Like a Dove Crying in a Ruin: Biblical and Rabbinic Intertexts in the Poetry of Isaac Shalev - Stein, Dina (MiKAN, 2022)
While Isaac Shalev’s poetry was received with great enthusiasm by a wide audience, it was heavily criticized by most of the literary establishment. The criticism was first and foremost motivated by a demand to follow modernist norms of Israeli poetry of that era, a demand that Shalev, an epic and sentimental poet, clearly did not comply with. It was also argued that Shalev failed to display a new stance vis-a-vis a major intertext—the bible. The article revisits the place of the biblical intertexts, as well as that of midrashic and rabbinic texts in general, in the poetics of Shalev’s poetry, poetics that indeed should be appreciated in relation to the predominant modernist criteria, without however subordinating it to critical measures which apply to the latter. The first part addresses the biblical stratum in Shalev’s poetry; the second and expanded part—focuses on the image of the ruin, borrowed from a rabbinic tale. The ruin, and especially the dove crying in a ruin, embodies themes and tensions which are central in Shalev’s poetry, rendering it at times far more complex, and self-doubting than it may appear.